(untitled) (Repertorio Científico, 2020)
ABSTRACT Introduction: The development of a new communication architecture sets new challenges, in the case of SDN in terms of management Objective: To analyze SDN networks management from the FCAPS perspective. Methods: Review of different sources of information such as scientific articles, supplier documents and regulations with which to make a comparison. Results: First, understanding management in SDN and its management protocol called OpenFlow and its differences with the traditional model and SNMP. Second, OpenFlow needs the plugins development to fully support all FCAPS functions Conclusions: First, SDN management is possible to be analyze and evaluate from the FCAPS perspective. Second, SDN management has gaps versus FCAPS model that are covered with complementary developments. Third, SDN can achieve all the functionalities in the short term due to the recent time that this architecture has in technological terms.